Preparation method of organosilicon copolymer loaded nano-silver modified epoxy coating
By adding silicone copolymer-loaded nanosilver to epoxy resin coatings, the problems of poor toughness and lack of antibacterial properties of epoxy resin coatings are solved, and the toughening and efficient antibacterial effects of the coatings are achieved.
Patent Information
- Application Number
- CN202411027803.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-30
AI Technical Summary
Epoxy resin coatings have poor toughness and no antibacterial properties, which limits their practical application in medical and health fields.
By preparing organic silicon cluster load nano-silver-modified epoxy coatings, the carboxyl-phthalate organic silicon cluster reacts with silver nitrate to form nano-silver, improve its decentralization, and add it to the epoxy resin.
It significantly improves the toughness and antibacterial properties of epoxy resin coatings, and enhances its application potential in the field of medical care.
Smart Images

Figure CN118852948B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy resins, and in particular relates to a method for preparing an epoxy coating modified by organic silicon copolymer loaded with nano-silver. Background Art
[0002] Antibacterial materials refer to materials that have the function of inhibiting and killing bacteria and microorganisms, mainly antibacterial coatings, antibacterial plastics, antibacterial fibers, etc., which are widely used in people's daily life and medical and health care. Antibacterial agents are usually added to the material matrix. Among them, nanosilver, as an inorganic antibacterial agent with excellent antibacterial properties, has the advantages of strong bactericidal properties, good broad-spectrum antibacterial properties, non-toxic and environmentally friendly, and small dosage. However, nanosilver is prone to agglomeration and has poor dispersion in the material matrix. Usually, when preparing nanosilver, polyvinyl pyrrolidone, chitosan, polyacrylic acid, etc. need to be added as stabilizers, which are beneficial to adjust the size of nanosilver and improve its dispersion.
[0003] Epoxy resin coatings have good film-forming properties, excellent anti-corrosion properties, and high mechanical strength. They are widely used in anti-corrosion coatings, insulation coatings, etc. However, epoxy resin coatings have poor toughness and are prone to cracking. Flexible polymers such as silicone, polyether, and nitrile rubber are usually used to toughen epoxy resins. In addition, epoxy resins do not have antibacterial properties, which limits their practical application in medical and health fields. Summary of the invention
[0004] The invention solves the problem that the epoxy resin coating has poor toughness and lacks antibacterial performance.
[0005] The technical solution provided by the present invention is: a method for preparing an organosilicon copolymer-loaded nanosilver-modified epoxy coating:
[0006] Step S1, add dimethyl sulfoxide solvent, aminopropyl-terminated polydimethylsiloxane, and 3,5-diaminobenzoic acid into a reaction container, stir to dissolve, add 5-(3,4-dihydroxybenzylamine)isophthalaldehyde, pass nitrogen, react, add methanol to dilute, filter, wash with methanol, and dry to obtain a carboxyl-catechol organosilicon copolymer.
[0007] Step S2, adding water and carboxyl-catechol organosilicon copolymer into a reaction container, stirring evenly, adding silver nitrate, stirring and adsorbing, then performing a reduction reaction, adding methanol to dilute, filtering, washing with methanol, and drying to obtain organosilicon copolymer loaded with nanosilver.
[0008] Step S3, adding water, water-based epoxy resin, organosilicon copolymer loaded with nano-silver, defoamer, leveling agent, and wetting agent into a container, stirring and dispersing, and then adding a curing agent to obtain organosilicon copolymer loaded with nano-silver modified epoxy coating.
[0009] Preferably, in step S1, the ratio of aminopropyl-terminated polydimethylsiloxane, 3,5-diaminobenzoic acid, and 5-(3,4-dihydroxybenzylamine)isophthalaldehyde is (88-95) mol:(5-12) mol:100 mol.
[0010] Preferably, in step S1, the reaction is carried out at 80-130° C. for 12-24 h.
[0011] Preferably, in step S1, the ratio of carboxyl-catechol organosilicon copolymer to silver nitrate is 100 g:(4-15) g.
[0012] Preferably, in step S2, the adsorption is carried out by stirring at 20-30°C for 3-5 hours; and the reduction reaction is carried out at 65-80°C for 1-2 hours.
[0013] Preferably, in step S3, the ratio of waterborne epoxy resin, organosilicon copolymer loaded with nanosilver, and curing agent is 100:(10-30):(2.2-3.2); the curing agent includes 2-ethyl-4-methylimidazole.
[0014] Preferably, the preparation method of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde is as follows: add ethanol solvent, 3,4-dihydroxybenzaldehyde and 3,5-di(hydroxymethyl)aniline to a reaction container, carry out condensation reaction at 30-45°C for 6-10h, concentrate the solution, add dichloromethane solvent and oxidant pyridinium chlorochromate, and control the ratio of 3,4-dihydroxybenzaldehyde, 3,5-di(hydroxymethyl)aniline and pyridinium chlorochromate to be 100mol:(90-110)mol:(300-350)mmol; carry out oxidation reaction at 20-30 for 2-3h, concentrate the solution, wash with ether, separate the crude product by silica gel column chromatography, and carry out gradient elution with petroleum ether and ethyl acetate solution to obtain 5-(3,4-dihydroxybenzylamine)isophthalaldehyde.
[0015] The technical effect of the present invention is: 3,4-dihydroxybenzaldehyde and 3,5-di(hydroxymethyl)aniline are subjected to Schiff base condensation reaction, and then the hydroxymethyl group is oxidized into an aldehyde group by using pyridinium chlorochromate to obtain 5-(3,4-dihydroxybenzyl imine)isophthalaldehyde, which contains two aldehyde groups and can undergo Schiff base polymerization reaction with aminopropyl-terminated polydimethylsiloxane and 3,5-diaminobenzoic acid to obtain a carboxyl-catechol organosilicon copolymer.
[0016] The Schiff base group of the main chain of the carboxyl-catechol organosilicon copolymer and the carboxyl group of the side chain play a complexing and stabilizing role on the silver ions of silver nitrate, and the silver ions are uniformly adsorbed in the organosilicon copolymer molecular chain. Then the catechol group of the side chain reduces the silver ions into nanosilver, so that the nanosilver grows uniformly on the organosilicon copolymer molecular chain, improves the dispersibility of the nanosilver, and reduces agglomeration. When added to epoxy resin coating, it shows obvious inhibition zone diameter for Escherichia coli and Staphylococcus aureus, and has excellent antibacterial performance.
[0017] The present invention adds an organosilicon copolymer loaded with nano-silver to an epoxy resin coating to modify the epoxy coating, wherein the side chain of the organosilicon copolymer contains a hydrophilic carboxyl group and a catechol group, which significantly improves the hydrophilicity of the organosilicon copolymer and has good dispersibility in water. The epoxy coating emulsion is transparent, uniform, non-stratified and has good dispersibility.
[0018] The side chain of the organic silicon copolymer of the present invention contains a carboxyl group. In the curing system of 2-ethyl-4-methylimidazole, the carboxyl group can undergo a ring-opening curing reaction with the epoxy group of the epoxy resin, thereby enhancing the bonding strength of the organic silicon copolymer and the epoxy resin and enhancing the compatibility of the two, so that the flexible polysiloxane molecular chain is chemically bonded to the curing system of the epoxy resin, thereby achieving a good toughening effect and significantly improving the elongation at break and the bending strength of the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the reaction formula for preparing 5-(3,4-dihydroxybenzylamine)isophthalaldehyde.
[0020] Figure 2 It is the reaction formula of carboxyl-catechol organosilicon copolymer. DETAILED DESCRIPTION
[0021] The following is a specific and detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given. It should be pointed out that for ordinary technicians in this technical field, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the scope of protection of the present invention.
[0022] The waterborne epoxy resin of the present invention is bisphenol A waterborne epoxy resin, with the brand CYDW100.
[0023] The defoamer brand is Foamaster MO 2134.
[0024] The leveling agent brand is BYK381.
[0025] The wetting agent brand is TEGO4100.
[0026] Aminopropyl terminated polydimethylsiloxane, molecular weight 2000. The structural formula is as follows:
[0027]
[0028] Example 1
[0029] (1) 35 mL of ethanol, 6 mmol of 3,4-dihydroxybenzaldehyde (CAS No. 139-85-5) and 6.6 mmol of 3,5-di(hydroxymethyl)aniline (CAS No. 71176-54-0) were added to a reaction container, and a condensation reaction was carried out at 35° C. for 10 hours. The solution was concentrated, and 40 mL of dichloromethane and 21 mmol of an oxidant, pyridinium chlorochromate (CAS No. 26299-14-9), were added, and an oxidation reaction was carried out at 20° C. for 3 hours. The solution was concentrated, washed with ether, and the crude product was separated by silica gel column chromatography, and gradient elution was carried out with petroleum ether and ethyl acetate solution to obtain 5-(3,4-dihydroxybenzylimido)isophthalaldehyde.
[0030] (2) Add 80 mL of dimethyl sulfoxide solvent, 9.5 mmol of aminopropyl-terminated polydimethylsiloxane, and 0.5 mmol of 3,5-diaminobenzoic acid (CAS No. 535-87-5) into a reaction container, stir to dissolve, add 10 mmol of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde, introduce nitrogen, react at 80° C. for 24 h, add methanol to dilute, filter, wash with methanol, and dry to obtain a carboxyl-catechol organosilicon copolymer.
[0031] (3) Add 200 mL of water and 20 g of carboxyl-catechol organosilicon copolymer to the reaction container, stir evenly, then add 0.8 g of silver nitrate, stir and adsorb at 30°C for 3 h, then perform reduction reaction at 70°C for 1 h, add methanol to dilute, filter, wash with methanol, and dry to obtain organosilicon copolymer loaded with nanosilver.
[0032] (4) Add 120 mL of water, 100 g of water-based epoxy resin, 10 g of organosilicon copolymer loaded with nanosilver, 0.8 g of defoamer, 0.2 g of leveling agent, and 0.5 g of wetting agent into a container and stir to disperse, then add 2.7 g of curing agent 2-ethyl-4-methylimidazole to obtain an organosilicon copolymer loaded with nanosilver modified epoxy coating.
[0033] Example 2
[0034] (1) Add 35 mL of ethanol, 6 mmol of 3,4-dihydroxybenzaldehyde, and 5.4 mmol of 3,5-di(hydroxymethyl)aniline to a reaction container, carry out condensation reaction at 30°C for 10 hours, concentrate the solution, add 30 mL of dichloromethane and 18 mmol of oxidant pyridinium chlorochromate, carry out oxidation reaction at 25 for 3 hours, concentrate the solution, wash with ether, separate the crude product by silica gel column chromatography, and perform gradient elution with petroleum ether and ethyl acetate solution to obtain 5-(3,4-dihydroxybenzylimido)isophthalaldehyde.
[0035] (2) Add 70 mL of dimethyl sulfoxide solvent, 9.2 mmol of aminopropyl-terminated polydimethylsiloxane, and 0.8 mmol of 3,5-diaminobenzoic acid into a reaction container, stir to dissolve, add 10 mmol of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde, introduce nitrogen, react at 130° C. for 12 h, add methanol to dilute, filter, wash with methanol, and dry to obtain a carboxyl-catechol organosilicon copolymer.
[0036] (3) Add 300 mL of water and 20 g of carboxyl-catechol organosilicon copolymer to the reaction container, stir evenly, then add 2 g of silver nitrate, stir and adsorb at 20°C for 5 h, then perform reduction reaction at 65°C for 2 h, add methanol to dilute, filter, wash with methanol, and dry to obtain organosilicon copolymer loaded with nanosilver.
[0037] (4) Add 120 mL of water, 100 g of water-based epoxy resin, 10 g of organosilicon copolymer loaded with nanosilver, 0.5 g of defoamer, 0.3 g of leveling agent, and 0.5 g of wetting agent into a container and stir to disperse, then add 2.2 g of curing agent 2-ethyl-4-methylimidazole to obtain an organosilicon copolymer loaded with nanosilver modified epoxy coating.
[0038] Example 3
[0039] (1) Add 40 mL of ethanol, 6 mmol of 3,4-dihydroxybenzaldehyde, and 6 mmol of 3,5-di(hydroxymethyl)aniline to a reaction container, carry out condensation reaction at 45°C for 6 hours, concentrate the solution, add 40 mL of dichloromethane and 20 mmol of oxidant pyridinium chlorochromate, carry out oxidation reaction at 30 for 2 hours, concentrate the solution, wash with ether, separate the crude product by silica gel column chromatography, and perform gradient elution with petroleum ether and ethyl acetate solution to obtain 5-(3,4-dihydroxybenzylimido)isophthalaldehyde.
[0040] (2) Add 50 mL of dimethyl sulfoxide solvent, 8.8 mmol of aminopropyl-terminated polydimethylsiloxane, and 1.2 mmol of 3,5-diaminobenzoic acid into a reaction container, stir to dissolve, add 10 mmol of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde, introduce nitrogen, react at 120° C. for 18 h, add methanol to dilute, filter, wash with methanol, and dry to obtain a carboxyl-catechol organosilicon copolymer.
[0041] (3) Add 300 mL of water and 20 g of carboxyl-catechol organosilicon copolymer to the reaction container, stir evenly, then add 3 g of silver nitrate, stir and adsorb at 20°C for 5 h, then perform reduction reaction at 80°C for 1 h, add methanol to dilute, filter, wash with methanol, and dry to obtain organosilicon copolymer loaded with nanosilver.
[0042] (4) Add 120 mL of water, 100 g of water-based epoxy resin, 10 g of organosilicon copolymer loaded with nanosilver, 0.8 g of defoamer, 0.6 g of leveling agent, and 0.3 g of wetting agent into a container and stir to disperse, then add 3.2 g of curing agent 2-ethyl-4-methylimidazole to obtain an organosilicon copolymer loaded with nanosilver modified epoxy coating.
[0043] Comparative Example 1
[0044] (2) Add 120 mL of water, 100 g of water-based epoxy resin, 0.8 g of defoamer, 0.2 g of leveling agent, and 0.5 g of wetting agent into a container, stir and disperse, and then add 2.7 g of curing agent 2-ethyl-4-methylimidazole to obtain an epoxy coating.
[0045] Comparative Example 2
[0046] (1) Add 80 mL of dimethyl sulfoxide solvent, 9.5 mmol of aminopropyl-terminated polydimethylsiloxane, and 0.5 mmol of 3,5-diaminobenzoic acid into a reaction container, stir to dissolve, add 10 mmol of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde (prepared in the same manner as in Example 1), introduce nitrogen, react at 80° C. for 24 h, add methanol to dilute, filter, wash with methanol, and dry to obtain a carboxyl-catechol organosilicon copolymer.
[0047] (2) Add 120 mL of water, 100 g of water-based epoxy resin, 10 g of carboxyl-catechol silicone copolymer, 0.8 g of defoamer, 0.2 g of leveling agent, and 0.5 g of wetting agent into a container, stir and disperse, and then add 2.7 g of curing agent 2-ethyl-4-methylimidazole to obtain a silicone copolymer modified epoxy coating.
[0048] Comparative Example 3
[0049] (1) Add 80 mL of dimethyl sulfoxide solvent and 10 mmol of aminopropyl-terminated polydimethylsiloxane into a reaction container, stir and dissolve, add 10 mmol of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde (prepared in the same manner as in Example 1), introduce nitrogen, react at 80° C. for 24 h, add methanol to dilute, filter, wash with methanol, and dry to obtain a catechol organosilicon copolymer.
[0050] (2) Add 200 mL of water and 20 g of catechol organosilicon copolymer to a reaction container, stir evenly, then add 0.8 g of silver nitrate, stir and adsorb at 30°C for 3 h, then perform reduction reaction at 70°C for 1 h, add methanol to dilute, filter, wash with methanol, and dry to obtain organosilicon copolymer loaded with nanosilver.
[0051] (3) Add 120 mL of water, 100 g of water-based epoxy resin, 10 g of organosilicon copolymer loaded with nanosilver, 0.8 g of defoamer, 0.2 g of leveling agent, and 0.5 g of wetting agent into a container and stir to disperse, then add 2.7 g of curing agent 2-ethyl-4-methylimidazole to obtain an organosilicon copolymer loaded with nanosilver modified epoxy coating.
[0052] The epoxy coating (without adding curing agent 2-ethyl-4-methylimidazole) was placed at room temperature for 30 days to observe the dispersion of the emulsion. The test results are shown in the table below.
[0053] Emulsion Dispersibility Example 1 Transparent, uniform, no stratification Example 2 Transparent, uniform, no stratification Example 3 Transparent, uniform, no stratification Comparative Example 1 Transparent, uniform, no stratification Comparative Example 2 Transparent, uniform, no stratification Comparative Example 3 Opaque, with a small amount of flocculent matter
[0054] After testing, the organosilicon copolymer-loaded nanosilver-modified epoxy coatings of Examples 1, 2, and 3 are transparent, uniform, and non-stratified. This is because the side chains of the organosilicon copolymers contain hydrophilic carboxyl and catechol groups, which significantly improve the hydrophilicity of the organosilicon copolymers, and have good dispersibility in water and good emulsion dispersibility.
[0055] The carboxyl-catechol organosilicon copolymer of Comparative Example 2 also contains hydrophilic carboxyl and catechol groups in its side chains, and has good dispersibility in water and good emulsion dispersibility.
[0056] The organosilicon copolymer loaded with nanosilver in Comparative Example 3 contains hydrophilic catechol groups but no carboxyl groups, has low hydrophilicity, and has poor dispersibility in water. The emulsion has a small amount of flocs and poor dispersibility.
[0057] The epoxy coating (with curing agent 2-ethyl-4-methylimidazole) was cast into a mold, first cured at 90°C for 3 hours, then cured at 120°C for 4 hours to make a casting specimen. The tensile properties and flexural strength were tested according to GB / T 2567-2021. The test results are shown in the table below.
[0058] Tensile strength(MPa) Elongation at break (%) Bending strength(MPa) Example 1 51.3 8.7 88.2 Example 2 50.1 9.4 86.0 Example 3 51.8 8.9 87.7 Comparative Example 1 42.5 4.6 73.9 Comparative Example 2 50.8 9.0 87.5 Comparative Example 3 45.0 6.1 77.3
[0059] In Examples 1, 2, and 3, organosilicon copolymers loaded with nanosilver are added to the epoxy resin coating. The side chains of the organosilicon copolymers contain carboxyl groups. In the curing system of 2-ethyl-4-methylimidazole, the carboxyl groups can undergo a ring-opening curing reaction with the epoxy groups of the epoxy resin, thereby enhancing the bonding strength of the organosilicon copolymer and the epoxy resin and the compatibility of the two, so that the flexible polysiloxane molecular chains are chemically bonded to the curing system of the epoxy resin, thereby achieving a good toughening effect. The elongation at break and the flexural strength of the epoxy resin reach 8.7-9.4%, and the flexural strength reaches 86.0-88.2 MPa, which are significantly higher than the epoxy coating in Comparative Example 1 in which no organosilicon copolymer loaded with nanosilver is added.
[0060] The epoxy resin coating of Comparative Example 2 is added with a carboxyl-catechol silicone copolymer, which contains a carboxyl group and can undergo a ring-opening reaction with the epoxy group of the epoxy resin, so that the flexible polysiloxane molecular chain is chemically bonded to the curing system of the epoxy resin, which has a good toughening effect, with an elongation at break reaching 9.0% and a flexural strength reaching 87.5 MPa.
[0061] The prepared silicone copolymer of Comparative Example 3 did not add 3,5-diaminobenzoic acid, which does not contain a carboxyl group and cannot undergo a curing reaction with the epoxy resin. It has poor compatibility with the epoxy resin and poor toughening effect. The elongation at break and the flexural strength are significantly lower than those in Example 1.
[0062] The epoxy coating was thermally cured to form a film sample with a thickness of 1 mm. Escherichia coli and Staphylococcus aureus were used as experimental bacteria, and the experimental bacteria were cultured and activated to form a film with a concentration of 10 7 cfu / mL bacterial suspension. Pipette 0.2mL of bacterial suspension and evenly coat it on the surface of beef extract peptone agar medium, then stick the film sample to the surface of the medium, place it in a constant temperature and humidity incubator, culture it at 37℃ for 24h, and measure the diameter of the inhibition zone. Each group of film samples was tested 3 times, and the average value of the inhibition zone diameter was taken. The test results are shown in the table below.
[0063]
[0064] The carboxyl-catechol organosilicon copolymers of Examples 1, 2, and 3 have carboxyl groups in the side chains and Schiff base groups in the main chains, which play a complexing and stabilizing role on the silver ions of silver nitrate, and uniformly adsorb the silver ions in the organosilicon copolymer molecular chains. Then, the catechol groups in the side chains reduce the silver ions to nanosilver, so that the nanosilver grows uniformly on the organosilicon copolymer molecular chains, thereby improving the dispersibility of the nanosilver and reducing agglomeration. When added to epoxy resin coatings, they show obvious inhibition zone diameters against Escherichia coli and Staphylococcus aureus, and have excellent antibacterial properties.
[0065] The epoxy coating of Comparative Example 1 does not contain nanosilver, and Comparative Example 2 adds carboxyl-catechol organosilicon copolymer, which also does not contain nanosilver. It does not show an inhibition zone diameter against Escherichia coli and Staphylococcus aureus and has no antibacterial property.
[0066] The catechol organosilicon copolymer of Comparative Example 3 contains only Schiff base groups and no carboxyl groups, and has low complexing and stabilizing effects on silver ions. After reduction with catechol, the generated nanosilver is prone to agglomeration and has poor dispersibility. When added to epoxy coatings, the diameter of the inhibition zone against Escherichia coli and Staphylococcus aureus is slightly lower than that of the embodiments.
[0067] Taking Example 1 as an example, the amount of the organosilicon copolymer loaded with nanosilver is controlled to be 10-30 g. The epoxy coating (without adding the curing agent 2-ethyl-4-methylimidazole) is placed at room temperature for 30 days to observe the dispersion of the emulsion.
[0068] The epoxy coating (with curing agent 2-ethyl-4-methylimidazole) was cast into a mold, first cured at 90°C for 3 hours, and then cured at 120°C for 4 hours to make a casting specimen. The tensile properties and flexural strength were tested according to GB / T 2567-2021.
[0069] The epoxy coating was thermally cured to form a film sample with a thickness of 1 mm. The diameter of the inhibition zone against Escherichia coli and Staphylococcus aureus was tested, and each group of film samples was tested 3 times, and the average value of the inhibition zone diameter was taken.
[0070] The test results are shown in the table below.
[0071]
[0072]
[0073] As can be seen from the above table, as the amount of nanosilver loaded on the silicone copolymer gradually increases, the emulsion dispersibility still has good emulsion dispersibility. The diameter of the inhibition zone of Escherichia coli and Staphylococcus aureus is getting larger and larger, showing excellent antibacterial properties. The tensile strength, elongation at break, and bending strength are significantly improved, but show a trend of first increasing and then decreasing.
[0074] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an organosilicon copolymer-loaded nanosilver-modified epoxy coating, characterized in that: The preparation method is: Step S1, adding dimethyl sulfoxide solvent, aminopropyl-terminated polydimethylsiloxane, and 3,5-diaminobenzoic acid into a reaction container, stirring to dissolve, adding 5-(3,4-dihydroxybenzyl imine)isophthalaldehyde, passing nitrogen gas, reacting, adding methanol to dilute, filtering, washing with methanol, and drying to obtain a carboxyl-catechol organosilicon copolymer; Step S2, adding water and carboxyl-catechol organosilicon copolymer to a reaction container, stirring evenly, adding silver nitrate, stirring and adsorbing, then performing a reduction reaction, adding methanol to dilute, filtering, washing with methanol, and drying to obtain organosilicon copolymer loaded with nanosilver; Step S3, adding water, water-based epoxy resin, organosilicon copolymer loaded with nano-silver, defoamer, leveling agent, and wetting agent into a container, stirring and dispersing, and then adding a curing agent to obtain organosilicon copolymer loaded with nano-silver modified epoxy coating.
2. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 1, characterized in that: In the step S1, the ratio of aminopropyl-terminated polydimethylsiloxane, 3,5-diaminobenzoic acid, and 5-(3,4-dihydroxybenzylamine)isophthalaldehyde is (88-95) mol:(5-12) mol:100 mol.
3. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 1, characterized in that: In the step S1, the reaction is carried out at 80-130° C. for 12-24 hours.
4. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 1, characterized in that: In the step S1, the ratio of carboxyl-catechol organosilicon copolymer to silver nitrate is 100 g:(4-15) g.
5. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 1, characterized in that: In the step S2, the adsorption is stirred at 20-30° C. for 3-5 hours; and the reduction reaction is carried out at 65-80° C. for 1-2 hours.
6. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 1, characterized in that: In the step S3, the ratio of waterborne epoxy resin, organic silicon copolymer loaded with nanosilver, and curing agent is 100:(10-30):(2.2-3.2); the curing agent includes 2-ethyl-4-methylimidazole.
7. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 2, characterized in that: The preparation method of 5-(3,4-dihydroxybenzylamine)isophthalaldehyde comprises the following steps: adding an ethanol solvent, 3,4-dihydroxybenzaldehyde and 3,5-di(hydroxymethyl)aniline into a reaction container to carry out a condensation reaction, concentrating the solution, adding a dichloromethane solvent and an oxidant pyridinium chlorochromate to carry out an oxidation reaction, concentrating the solution, washing with ether, separating the crude product by silica gel column chromatography, and gradient eluting with petroleum ether and ethyl acetate solution to obtain 5-(3,4-dihydroxybenzylamine)isophthalaldehyde.
8. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 7, characterized in that: The ratio of the 3,4-dihydroxybenzaldehyde, 3,5-di(hydroxymethyl)aniline and pyridinium chlorochromate is 100 mol:(90-110) mol:(300-350) mmol.
9. The method for preparing the organosilicon copolymer-loaded nanosilver-modified epoxy coating according to claim 7, characterized in that: The condensation reaction is carried out at 30-45°C for 6-10 hours; the oxidation reaction is carried out at 20-30°C for 2-3 hours.
Citation Information
Patent Citations
Frequency modulated relaxation oscillator
CA535875A
Main chain degradation type metal ion complexation poly-Schiff base antifouling resin, preparation method and application
CN113698561A
Organosilicone modified styrene acrylate self-emulsifying emulsion, preparation method and antifouling high-color-fastness water-based paint prepared based on organosilicone modified styrene acrylate self-emulsifying emulsion
CN115109199A